Study of the fracture process in heterogeneous materials around boreholes filled with expansion cement. (1st May 2017) - Tang, S.B.; Huang, R.Q.; Wang, S.Y.; Bao, C.Y.; Tang, C.A.
Abstract: A numerical model is proposed to study crack initiation, propagation and coalescence in heterogeneous materials subjected to expansion pressure in boreholes using the finite element method and damage mechanics. The strength heterogeneity of materials is modeled at the mesoscopic level using the Weibull distribution. Using this numerical model, the initiation and propagation of cracks generated by expansion cement in boreholes were simulated. The numerical simulations qualitatively reproduced the crack patterns in samples tested in laboratory experiments. Moreover, the results clarified the failure mechanisms and fracture processes, thereby contributing to a better understanding of fracture mechanisms in heterogeneous materials subjected to expansion pressure in boreholes. The numerical model allows direct observation of the entire process of crack initiation and growth to a degree that would be difficult to obtain in experimental studies.